SIK2 expression in retinal cells and its possible involvement along with PKA in FGF9 signal transduction - Özmen, Yeşim. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
FGF signal transduction pathway activates a cascade of kinase and phosphatase dependent phosphorylation and dephosphorylation events. The pathway is subject to tight control mechanisms through negative feedback exerted by the the activated effector molecules, action of kinases and phosphatases. Besides the cellular context and interplay between the regulators, integration of heterologous signaling is also critical in shaping the cellular responses. In this study, we have shown FGF9 receptors FGFR2, FGFR3 and a putative modulator SIK2 is widely expressed in neuronal cells and Muller glia, FGF9 is detected in neuronal cell layers but not in Muller cells. Our data, when compared with the primary Muller cells, indicate that MIO-M1 cells are equipped with the components of signal transduction. Using these cells as model system we had shown the activation of FGF9 pathway and that the pathway is modulated by PKA activity. We had also shown that SIK2 is modulated both in response to PKA and FGF9 by phosphorylation and nuclear translocation. Regulation of SIK2 translocation correlates with levels of ERK phosphorylation. When both stimuli are present SIK2 tends to act in accordance with FGF9 but not PKA.
Keywords: Fibroblast growth factors.; Cellular signal transduction.; Protein kinases.; Retina.